2017
DOI: 10.1007/s12020-017-1316-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of Cushing’s disease with pasireotide: 5-year results from an open-label extension study of a Phase III trial

Abstract: BackgroundTreating hypercortisolism in patients with Cushing’s disease after failed surgery often requires chronic medication, underlining the need for therapies with favourable long-term efficacy and safety profiles.MethodsIn a randomised, double-blind study, 162 adult patients with persistent/recurrent or de novo Cushing’s disease received pasireotide. Patients with mean urinary free cortisol at/below the upper limit of normal or clinical benefit at month 12 could continue receiving pasireotide during an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…In line with the previous evidence, the observed improvements were similar in FC, PC, and UC patients, confirming that pasireotide effects on clinical picture and metabolic profile were present also in patients with cortisol reduction, although mostly evident in patients with complete normalization of cortisol secretion. Interestingly, these results seem to confirm not only data of the phase III study, but also data reported in different studies, mainly small series or case reports [23][24][25][26][27][28][29][30], published during the last years, that have documented improvements in signs and symptoms [23][24][25][26][27][28], BW [22,23,[26][27][28][29], WC [26][27][28][29], blood pressure [22,23,[25][26][27][28][29][30], and lipid profile [28].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with the previous evidence, the observed improvements were similar in FC, PC, and UC patients, confirming that pasireotide effects on clinical picture and metabolic profile were present also in patients with cortisol reduction, although mostly evident in patients with complete normalization of cortisol secretion. Interestingly, these results seem to confirm not only data of the phase III study, but also data reported in different studies, mainly small series or case reports [23][24][25][26][27][28][29][30], published during the last years, that have documented improvements in signs and symptoms [23][24][25][26][27][28], BW [22,23,[26][27][28][29], WC [26][27][28][29], blood pressure [22,23,[25][26][27][28][29][30], and lipid profile [28].…”
Section: Discussionsupporting
confidence: 88%
“…Notably, in these large experiences, UFC reduction was accompanied by improvements in symptoms and signs as well as in metabolic profile and comorbidities of CD, also maintained during long-term treatment [10][11][12]23]. Facial rubor, supraclavicular and dorsal fat pads, and bruising improved, whereas BW, BMI, WC, blood pressure, total and LDL cholesterol were significantly reduced, as well as depression and QoL scores improved [10][11][12].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…14 Cardiovascular disease is the leading cause of death in patients with CD. 14 Cardiovascular disease is the leading cause of death in patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the long-term efficacy of pasireotide and are consistent with findings from a Phase III study, in which 69% (n = 11/16) of ongoing patients had controlled mUFC after 5 years of twice-daily, subcutaneous pasireotide therapy. 14 Note: AEs are sorted in descending order of events during the extension. Patients who experienced an AE during the core study (months 0-12) and the extension (after month 12) are counted in both columns.…”
Section: Discussionmentioning
confidence: 99%